Do Demographic Factors Moderate How Well Criminal Thinking Predicts Recidivism?. (May 2018) - Folk, Johanna B.; Stuewig, Jeffrey B.; Blasko, Brandy L.; Caudy, Michael; Martinez, Andres G.; Maass, Stephanie; Taxman, Faye S.; Tangney, June P.
Is the relationship between criminal thinking and recidivism the same for criminal justice–involved individuals from varying demographic backgrounds? Relying on two independent samples of offenders and two measures of criminal thinking, the current studies examined whether four demographic factors—gender, race, age, and education—moderated the relationship between criminal thinking and recidivism. Study 1 consisted of 226 drug-involved probationers enrolled in a randomized clinical trial. Study 2 consisted of 346 jail inmates from a longitudinal study. Logistic regression models suggested that the strength of the relationship between criminal thinking and subsequent recidivism did not vary based on participant demographics, regardless of justice system setting or measure of criminal thinking. Criminal thinking predicts recidivism similarly for people who are male, female, Black, White, older, younger, and more or less educated.